L-band scintillations and calibrated total electron content gradients over Brazil during the last solar maximum - Cesaroni, Claudio; Spogli, Luca; Alfonsi, Lucilla; De Franceschi, Giorgiana; Ciraolo, Luigi; Galera Monico, Joao Francisco; Scotto, Carlo; Romano, Vincenzo; Aquino, Marcio; Bougard, Bruno (EDP Sciences, 2015)
This work presents a contribution to the understanding of the ionospheric triggering of L-band scintillation in the region over São Paulo state in Brazil, under high solar activity. In particular, a climatological analysis of Global Navigation Satellite Systems (GNSS) data acquired in 2012 is presented to highlight the relationship between intensity and variability of the total electron content (TEC) gradients and the occurrence of ionospheric scintillation. The analysis is based on the GNSS data acquired by a dense distribution of receivers and exploits the integration of a dedicated TEC calibration technique into the Ground Based Scintillation Climatology (GBSC), previously developed at the Istituto Nazionale di Geofisica e Vulcanologia. Such integration enables representing the local ionospheric features through climatological maps of calibrated TEC and TEC gradients and of amplitude scintillation occurrence. The disentanglement of the contribution to the TEC variations due to zonal and meridional gradients conveys insight into the relation between the scintillation occurrence and the morphology of the TEC variability. The importance of the information provided by the TEC gradients variability and the role of the meridional TEC gradients in driving scintillation are critically described.